Ultrasonographically visible hepatic location in clinically normal horses. Issue 6 (June 2016) - Johns, IC; Miles, A
Abstract : Objective: Ultrasound is widely used for evaluating horses with suspected liver dysfunction. Although a change in size is considered suggestive of pathology, no clear guidelines exist to define the hepatic ultrasonographically visible locations (HUVL) in horses. The aim of the study was to describe the HUVL in normal horses and determine whether this is altered by signalment, height, weight and body condition score (BCS). Design: Prospective observational study. Procedure: Bilateral ultrasonographic evaluation was performed in 58 clinically normal horses with no history of hepatic disease. The most cranial/caudal intercostal spaces (ICS), total number of ICS in which the liver was visualised and the ventral extent of the liver were recorded. Results: Liver was visualised on the right in 56/58 horses (97%), the left in 41/58 (71%) and on both sides in 39/58 (67%). The most cranial ICS was 5 (right) or 4 (left) and the most caudal was 16 (right) or 11 (left). Liver was visualised in ICS 0–11 (right) and ICS 0–5 (left). Liver was not visualised ventral to the costochondral junction. There was no significant effect of sex, breed, height, weight or BCS on HUVL. Liver was visible in significantly fewer ICS on the right in horses aged 24 years and older (median ICS 3.5) compared with younger horses (median ICS 7; P = 0.016). Conclusion: These findings suggest that the liver should be consistently visualised on the right side, but absence of ultrasonographically visible liver on the left is unlikely to be clinically relevant. Liver dimensions may be decreased in older horses.